Efficient and selective initiation by yeast RNA polymerase B in a dinucleotide-primed reaction. - Lescure, B (1981)
Yeast RNA polymerase B catalyzes an efficient abortive initiation on double-stranded DNA templates using the appropriate combination of primer and substrate. The specificity of initiation was investigated using a recombinant plasmid (pJD14 DNA) containing the structural gene for yeast alcohol dehydrogenase I (ADHI). The combination of the dinucleotide UpA and UTP was 10 fold more efficient with pJD14 DNA than with the vector pBR322 DNA to direct the synthesis of the trinucleotide UpApU. Under these conditions, stable enzyme-DNA complexes were formed and could be retained on nitrocellulose filters. Using the UpA-primed system and a short pulse of RNA synthesis, transcription complexes were located on the yeast part of pJD14 DNA as evidenced by agarose gel electrophoresis. Southern hybridization of the pulsed RNA was restricted to a region, within the yeast DNA fragment, upstream to the initial region of the ADHI gene.